2004
DOI: 10.1002/aoc.755
|View full text |Cite
|
Sign up to set email alerts
|

The microstructure of ferrofluids and their rheological properties

Abstract: One of the most important features of ferrofluids is the possibility to change their physical properties, especially their viscosity, by means of moderate magnetic fields. This capability makes ferrofluids very useful in the fields of engineering, medicine and fundamental research. Rheological experimental results, as well as theoretical studies, correlate the change of the viscosity of a sheared ferrofluid under the influence of a magnetic field, the so-called magnetoviscous effect, to the internal structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 8 publications
4
19
0
Order By: Relevance
“…However, at constant shear rate the viscosity increases with increase in the magnetic field (Fig. 4) until it reaches a saturation point which is in agreement with the Pop et al findings [42]. For FF, the viscosity is determined by the viscosity of carrier liquid (water) and the interaction of MNPs.…”
Section: Rheological Property Of Magnetic Fluidsupporting
confidence: 89%
“…However, at constant shear rate the viscosity increases with increase in the magnetic field (Fig. 4) until it reaches a saturation point which is in agreement with the Pop et al findings [42]. For FF, the viscosity is determined by the viscosity of carrier liquid (water) and the interaction of MNPs.…”
Section: Rheological Property Of Magnetic Fluidsupporting
confidence: 89%
“…4e and f). The agreement with the qualitative model developed to explain the macroscopical behaviour of ferrofluids [9] is confirmed also by the scattering curves obtained for Co ferrofluids. The radial averaged intensity plotted as a function of the scattering vector (Q) shows no dependence on the shear rate for the situation without magnetic field (see Fig.…”
Section: Article In Presssupporting
confidence: 82%
“…Also, it is found that SðK xz Þ increases in the high-K xz region as the magnetic field increases. Our results can be used to interpret experimental observations as obtained in a recent work [19] on the anisotropic structure of colloidal ferrofluids.…”
Section: Article In Presssupporting
confidence: 69%